Evolution of ISO's space debris mitigation standards. Issue 3 (September 2020) - Stokes, H.; Akahoshi, Y.; Bonnal, C.; Destefanis, R.; Gu, Y.; Kato, A.; Kutomanov, A.; LaCroix, A.; Lemmens, S.; Lohvynenko, A.; Oltrogge, D.; Omaly, P.; et al.
Abstract: Since 2010 the International Organization for Standardization (ISO) has been publishing a comprehensive set of international standards on space debris mitigation based on guidelines and best practices from the IADC and other bodies. This paper describes the structure and content of the ISO debris standards and how they are evolving to address the needs of space environment sustainability within the context of a rapidly changing space industry. Particular emphasis is placed on ISO 24113 (Space systems – Space debris mitigation requirements), which was published as a third edition during July 2019. The new requirements are compared with those in the previous edition and the rationale for the various changes is discussed. Most notably, the requirement for a spacecraft or orbital stage to exceed a specified threshold for its probability of successful disposal has been made more demanding. With the launch of numerous small spacecraft into LEO and the imminent launch of constellation systems comprising thousands of satellites, it is likely that the ISO debris standards will have to implement even stricter requirements in the future. The challenge is to do this in a way that is fair and reasonable for the entire space industry.